Bidirectional Mendelian Randomization Analysis of the Association Between Mitochondrial Proteins and Neurodegenerative Diseases - Fangyuan Wang; Zhou Jing; Qingyi Wang; Minghe Li; Bingqi Lu; Ao Huo; Chenglin Zhao; Huanyu Zhou; Wulong Liang; Weihua Hu; Xudong Fu (Brain and Behavior)
ABSTRACT Background Neurodegenerative diseases involve progressive neuronal dysfunction and cognitive decline, posing substantial global challenges. Although the precise causes remain unclear, several studies highlight the role of protein metabolism abnormalities in disease development. This study investigates the causal links between variations in mitochondrial protein genes and neurodegenerative diseases, aiming to elucidate their potential contributions to disease progression and identify novel therapeutic strategies. Methods Herein, we utilized data from genome‐wide association studies (GWAS) on mitochondrial proteins and neurodegenerative diseases. Bidirectional Mendelian randomization (MR), employing instrumental variables (IVs), was used to assess causal relationships. The primary method for estimating causal effects was the inverse variance‐weighted (IVW) method, supplemented by additional MR approaches. Results Bidirectional MR revealed significant associations between mitochondrial protein gene variants and neurodegenerative diseases. Specifically, associations were found with Alzheimer's disease (AD) (three proteins), Parkinson's disease (PD) (four proteins), amyotrophic lateral sclerosis (ALS) (six proteins), multiple sclerosis (two proteins), and dementia with Lewy bodies (four proteins). Conversely, analyses indicated significant associations of neurodegenerative diseases with mitochondrial protein gene variants, notably with AD, dementia with Lewy bodies, and multiple sclerosis, affecting multiple mitochondrial protein levels. Bidirectional causality was observed between dementia with Lewy bodies and C21orf33. Conclusions Using MR, we identified significant links between mitochondrial protein gene mutations and the risk of neurodegenerative diseases. These results highlight reciprocal relationships where certain neurodegenerative diseases influence mitochondrial protein expression levels. These findings underscore the pivotal role of mitochondrial proteins in neurodegenerative diseases, offering critical insights into disease mechanisms and potential therapeutic avenues.